Ekosistem Halal Rumah Potong Hewan: Studi Kasus Juru Sembelih Halal U.D. Dragon Broiler dan Sinar Raya Abadi - Setiawan, Yusuf; Nurhidayati; Lathifah, Auliya (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Slaughter person has an important role in determining the halalness and quality of the meat. Slaughterperson competence has been regulated in SKKNI No. 196 of 2014 concerning Indonesian national work competency standards for the categories of agriculture, forestry and fisheries, main groups of livestock support services in the field of halal animal slaughter. However, what happens between understanding the material during training and practice in the field is not easy to implement. This study aims to explore the understanding gaps of halal butchers about the critical points of halal slaughter in poultry at UD Dragon Broiler, Bantul and Sinar Raya Abadi, Sleman. The research method used was qualitative through observational data collection techniques and direct interviews with the butchers in charge of slaughtering at the slaughterhouse. The results of the study found that UD Dragon Broiler already has a certified halal slaughterman but acts as a supervisor, not a slaughterman, there are no banners containing procedures for the halal slaughter system, it's just that there is the word bismilah allahu akbar, and the competence of the slaughterers is based on experience, while RPA Sinar Raya Abadi do not yet have a certified halal slaughterman, there is a SOP for halal slaughter but it is very small, and the competence of the slaughterer is based on experience.